Early Vascular Aging in Hypertension - Nilsson, Peter M. (Frontiers in Cardiovascular Medicine, 2020)
With increasing age, the cardiovascular risk increases, as does frailty, with negative health consequences such as coronary disease, stroke, and vascular dementia. However, this aging process seems to take a more rapid course in some individuals, as reflected in the Early Vascular Aging (EVA) syndrome that over the recent 10 years has attracted increased attention. The core of the EVA syndrome is arterial stiffness in the media layer of large elastic arteries, a process that can be measured by pulse wave velocity, for example, along the aorta. Hypertension is a well-known cardiovascular risk factor in its own right, but also linked to the EVA process. However, several studies have shown that non-hemodynamic factors also contribute to arterial stiffness and EVA, such as impaired glucose metabolism, chronic inflammation, and oxidative stress. New perspectives have been introduced for linking early life programming affecting new-born babies and birth weight, with a later risk of hypertension, arterial stiffness and EVA. New drugs are being developed to treat EVA when lifestyle intervention and conventional risk factor controlling drugs are not enough. Finally, the opposite phenotype of EVA is Healthy Vascular Aging (HVA) or even Super Normal Vascular Aging (SUPERNOVA). If protective mechanisms can be found and mapped in these fortunate subjects with a slower than expected aging process, there could exist a potential to find new drug targets for preventive therapy.